A Causal Model of Adherence to Therapeutic Regimens Among Older Adults with Hypertension - Arunya Namwong (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Adherence to therapeutic regimens among older adults with hypertension results in appropriate blood pressure control. Knowledge of factors affecting adherence behaviors are needed to enhance adherence to therapeutic regimens among older adults with hypertension. A descriptive, cross-sectional, predictive correlational design was used to identify and test a causal relationship between cognitive function, physical function, social support from family, provider-patient communication, knowledge of hypertension, perceived benefits, perceived susceptibility, perceived severity, perceived barriers, perceived self-efficacy to adherence and adherence to therapeutic regimens among older adults with hypertension. A total of 341 hypertensive older adults with hypertension aged between 60-88 years were randomly selected from five hypertension clinics at community hospitals in Phayao Province, Thailand. All self-reported questionnaires with acceptable reliability coefficients were used to collect data. Data were analyzed using descriptive statistics, Pearson’s product moment correlation and path analysis by structural equation modeling.